2016
DOI: 10.3389/fendo.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings Show Maternal Hypothyroidism May Contribute to Abnormal Cortical Morphology in Offspring

Abstract: In rodents, insufficient thyroid hormone (TH) gestationally has adverse effects on cerebral cortex development. Comparable studies of humans examining how TH insufficiency affects cortical morphology are limited to children with congenital hypothyroidism or offspring of hypothyroxinemic women; effects on cortex of children born to women with clinically diagnosed hypothyroidism are not known. We studied archived MRI scans from 22 children aged 10–12 years born to women treated for preexisting or de novo hypothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Studies from Canada (7, 9, 10) evaluated MRI scans of 20-30 children aged 9-14 years born to mothers who were treated with L-T4 in the pregnancy for previously or newly diagnosed hypothyroidism and matched controls. In these studies (7,9,10), children born to mothers with hypothyroidism had smaller volume of the hippocampus, abnormal development of the corpus callosum and abnormal cortical morphology. Studies performed within the Generation R birth cohort in the Netherlands (8, 11) investigated MRI scans of 650 children aged 8 years.…”
Section: Thyroid Hormones and Brain Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies from Canada (7, 9, 10) evaluated MRI scans of 20-30 children aged 9-14 years born to mothers who were treated with L-T4 in the pregnancy for previously or newly diagnosed hypothyroidism and matched controls. In these studies (7,9,10), children born to mothers with hypothyroidism had smaller volume of the hippocampus, abnormal development of the corpus callosum and abnormal cortical morphology. Studies performed within the Generation R birth cohort in the Netherlands (8, 11) investigated MRI scans of 650 children aged 8 years.…”
Section: Thyroid Hormones and Brain Developmentmentioning
confidence: 96%
“…Recent studies including data on brain MRI scans from children born to mothers with thyroid dysfunction have demonstrated structural defects in the brain (7,8,9,10,11). However, most studies in humans include indicators of exposure or outcome and are observational in design, which may challenge the interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Brain structural changes were also described for more pronounced levels of maternal thyroid dysfunction. Particularly, small studies from Canada reported reduced hippocampal volumes, abnormal development of corpus callosum, and abnormal cortical morphology in children aged 9–14 years born to women who were treated with levothyroxine during pregnancy for previously or newly detected hypothyroidism (Lischinsky, Skocic, Clairman, & Rovet,; Samadi, Skocic, & Rovet, ; Willoughby, McAndrews, & Rovet, ).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…The first studies on maternal thyroid function and offspring neuroimaging outcomes were performed by the group of Rovet et al They composed a study population consisting of 20‐24 children (~30% of an original birth cohort) born from mothers that were undertreated for overt hypothyroidism (HYPO group) during at least a part of pregnancy, and 20‐30 healthy controls. The group of children in the HYPO group had smaller hippocampi, differently sized sub regions of the corpus callosum and unilateral thinning or thickening of certain (unilateral) cortical regions at the age of 10‐12 years . In addition, interesting hints towards dose‐dependent effects and differences according to thyroid dysfunction severity were identified .…”
Section: Clinical Studiesmentioning
confidence: 96%